Observations on the Effect of Glass Beads on Platelet Aggregation and Its Relation to Platelet Stickiness - Morris, C. D. W (Thrombosis and Haemostasis, 1968)
1. The concept of glass bead induced reversible and irreversible platelet aggregation is presented.2. The effect of glass beads in plasma and whole blood was observed microscopically. The microscopic observations were supported by experimental evidence.3. It is shown that phosphoenol pyruvate (PEP) and pyruvate kinase (PK) are capable of completely preventing aggregation if given before glass bead contact. This indicates that adenosine diphosphate (ADP) is the major factor in stimulating aggregation.4. It is shown that the ADP is released in this system, from the platelets, and not from the red cells.5. Haematocrit changes between 20% and 60% do not affect the platelet stickiness.6. The concentration of ADP apparently determines whether the aggregates become irreversible or not.7. Siliconised glass beads do not prevent aggregation; on the contrary, they increase both the observed rate of formation of aggregates, and the measured platelet stickiness.8. Addition of PEP and PK after glass contact causes the reversible aggregates to disaggregate. However, merely leaving the blood to stand for at least 30 min after contact, produces the same effect. This allows the measurement of pure irreversible aggregation.9. The desirability of measuring the irreversible aggregation is discussed.